Sex Differences in the Risk of Barrett's Esophagus Associated With the Metabolic Effects of Obesity. Issue 9 (October 2020) - Kendall, Bradley J.; Macdonald, Graeme A.; Prins, Johannes B.; O'Brien, Suzanne; Thrift, Aaron P.; Whiteman, David C.
Abstract : Goal: The goal of this study was to determine if there is an association between the insulin–insulin-like growth factor axis, the metabolic syndrome (MetS), type 2 diabetes mellitus and risk of Barrett's esophagus (BE), and if these associations are modified by sex. Background: BE is more common in males. Gastroesophageal reflux disease, the major risk factor for BE occurs at similar frequencies in both sexes, suggesting that sex-related factors such as the metabolic effects of abdominal obesity may be important in the causation of BE. Materials and Methods: A structured interview, anthropometric measures, and fasting blood were collected within a population-based case-control study. We recruited 227 BE cases (70% male) and 241 population controls, frequency matched by age and sex. We estimated odds ratios (ORs) and 95% confidence intervals (CIs) for association with BE using multivariable logistic regression models. Results: Hyperinsulinemia (highest vs. lowest tertile, OR=1.9; 95% CI: 1.2-3.1), Homeostatic Model Assessment of Insulin Resistance (OR=1.9; 95% CI: 1.2-3.1) and the MetS (OR=1.8; 95% CI: 1.2-2.6) were independently associated with an increased risk of BE. With each additional MetS criterion, there was a 20% increased risk of BE (OR=1.2; 95% CI: 1.0-1.4). When stratified by sex, these associations were found in males but not females. We found no association with serum measures of insulin-like growth factors or interleukin-6 and risk of BE. Conclusion: Hyperinsulinemia, insulin resistance, and the MetS are associated with the risk of BE in males but not females, suggesting these factors may contribute to the higher prevalence of BE in males. Abstract : Supplemental Digital Content is available in the text.